Toward Healthy Diets from Sustainable Food Systems. Issue 6 (20th May 2020) - Drewnowski, Adam; Finley, John; Hess, Julie M; Ingram, John; Miller, Gregory; Peters, Christian
Abstract: This article is based on a session at ASN 2019 entitled "Addressing the Four Domains of Sustainable Food Systems Science (Health, Economics, Society and the Environment): What Will It Take to Harmonize the Evidence to Advance the Field?" A summary of presentations is included. The presentations addressed the 4 principal domains of sustainability defined as nutrition/health, economics, environment, and society and the ways in which they are represented in current research. The session also introduced metrics and measures that are specific to each domain. Participants discussed next steps to move toward consensus and collaboration among scientific communities, especially those of health/nutrition science and environmental science. Food systems may need to be restructured to ensure that the global food supply provides adequate calories and nutrients at an affordable cost. Finally, the session addressed strategies to implement research concepts and move toward policies that encourage consumers to choose healthy diets from sustainable food systems.